The Use of Papaya (Carica papaya) Leaf Extract as a Natural Insecticide to Controlling Flies (Stomoxys sp.) in Cattle at Manokwari West Papua - Maria Herawati; Ni Putu Vidia Tiara Timur (Bantara Journal of Animal Science, 2022)
This study aims to determine the effect of using papaya leaf extract (Carica papaya) as a natural insecticide in controlling flies (Stomoxys sp.) and to determine its potential as a natural insecticide in terms of economic aspects. The results of this study can be a source of information and contribute to the handling of cage flies as vectors of disease spread in cattle that are environmentally friendly, inexpensive and easy to obtain. This research was conducted at Campus II of the Manokwari Agricultural Development Polytechnic Teaching Factory Unit, Anday. The material used 15 cattle which were grouped into 5 groups and each group consisted of 3 cattle. Each group was given negative control/clean water (P0), papaya leaf extract 100% (P1), papaya leaf extract 75% (P2), papaya leaf extract 50% (P3), and positive control or synthetic insecticide (P4). The method of using the treatment is by spraying it on the cattle on the neck and shoulders. The result showed that the treatment P4 had the longest resistance to being infested by flies compared to other treatments, followed by treatments P1, P2, P3, and P0. The most effective administration of papaya flies in cattle was treatment P1, because it had a lower fly perch than treatment P2, P3 and P0.